Pengembangan Pesantrenpreneur Pada Pesantren Ma’had Taqwa Center, Ciampea, Kabupaten Bogor - Purba, Jan Horas Veryady; Sukamto, Anton; gendalasari, Gen Gen; Trifena, Trifena; Chasanah, Ratu Ainurisa (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
Islamic boarding school education is divided into two types: salaf (traditional) Islamic boarding schools and khalaf (modern) Islamic boarding schools. The Ma'had Taqwa Center Islamic boarding school in Ciampea, Bogor has land resources that can be developed into productive activities. Two problems are found in this Islamic boarding school, namely (1) Lack of understanding in the management and marketing aspects of the Islamic boarding school. Target partners need training to improve resources consisting of students and Islamic boarding school managers to become entrepreneurs, and (2) Lack of understanding of social aspects of society. The objectives of this community service activity are: (1) to empower students and Islamic boarding school administrators to solve several problems faced by target partners to improve the resources of students and Islamic boarding school administrators, and (2) to help target partners to be able to obtain highly nutritious food, maintain their health and have a source of clean water for daily needs. The solutions developed include three important things, namely providing training and practice in hydroponic management, tilapia cultivation and broiler chicken farming. This activity is accompanied by the provision of the necessary facilities. This step is a strategic step in developing Islamic boarding school entrepreneurs, by fostering the entrepreneurial spirit of the students, as well as utilizing the potential of available land resources to be productive. Key words: hydroponics, pesantrenpreneur, entrepreneurship